MEDIA BRANDING IN JAVANESE LOCAL MEDIA “PANJEBAR SEMANGAT” - Ratih Pandu Mustikasari; Oktifani Winarti; Hanna Nurhaqiqi (JARES (Journal of Academic Research and Sciences), 2021)
The digital era is exposing the media industry and the audience to a new phenomenon, it is convergence. Convergence becomes a real challenge have to be faced by the entire media industry, from global to local media industries. The convergence faced by local media is a bigger challenge due to limited financial and resources. Various studies show that adaptation is mostly done by utilizing platforms in new media to re-embrace segmentation and even add new audience segmentations. The forms of adaptation presented show the elements of branding media in it. According to Malmelin and Moisander (2014) there are five concepts of branding media that are often used, they are brand extension, brand as identity, brand as differentiation, brand as equity, and brand as a product. This article will show the side of branding media by the local Javanese language magazine "Panjebar Semangat" in the middle of adaptation efforts to convergence. The discussion will be related to the five concepts presented by Malmelin and Moisander (2014). The method used in this research is descriptive qualitative. Data collection was carried out by interview and observation on the Panjebar Semangat social media account. The results show that the branding media activities carried out by Panjebar Semangat are dominated by the concept of brand extension and brand as a product. The branding media can also give well benefit by local media with limited funding sources to optimize adaptation to convergence.